2016
DOI: 10.12924/johs2016.12010091
|View full text |Cite
|
Sign up to set email alerts
|

Review of On-Scene Management of Mass-Casualty Attacks

Abstract: Background: The scene of a mass-casualty attack (MCA) entails a crime scene, a hazardous space and a great number of people needing medical assistance. Public transportation has been the target of such attacks and involves a high probability of generating mass casualties. The aim of the review was to investigate challenges for on-scene responses to MCAs and suggestions made to counter these challenges, with special attention given to attacks on public transportation and associated terminals. Methods: Articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 106 publications
(567 reference statements)
0
23
0
Order By: Relevance
“…Negative competition and contrast of interests among these organizations were also evident in our findings. Hence programming and coordinating police, rescue and aid teams, and EMS is an essential measure for managing mass casualty incidents, as suggested by others ( 27 ). The participants believed that having only one emergency and rescue phone number can coordinate the arrival time of different organizations and improve management of incidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative competition and contrast of interests among these organizations were also evident in our findings. Hence programming and coordinating police, rescue and aid teams, and EMS is an essential measure for managing mass casualty incidents, as suggested by others ( 27 ). The participants believed that having only one emergency and rescue phone number can coordinate the arrival time of different organizations and improve management of incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of an EOC can be a good way to create coordination among the organizations. Holgerson also concluded that absence of a centralized command system was one of the problems of onsite management in mass casualty traffic incidents ( 27 ). Lack of centralized command system at crash scene was mentioned by our participants as a managerial problem.…”
Section: Discussionmentioning
confidence: 99%
“…According to the evidence hierarchy used in the study (c.f. [19]) none of the included literature were systematic reviews or cross-sectional studies, but there were three high-quality modelling studies. Thirteen of the reviewed articles were medium-quality studies; one comparative case study and 12 case studies.…”
Section: Screening For Relevance and Qualitymentioning
confidence: 99%
“…Different triage systems have been designed for organizational, situational, regional, and national use, and have been presented as crude algorithms, flowcharts, and complex scoring systems [ 6 – 8 , 10 , 15 ]. This heterogeneity constitutes a threat in the event of an MCI, which often involves multinational and multiagency rescue teams with diverse educational and cultural backgrounds [ 2 , 16 , 17 ]. There have been several attempts to achieve a global or even national consensus without any results, partly due to a lack of actual research behind the origin or refinements of the various systems and the anecdotal nature of the evidence of a system’s efficacy [ 11 , 17 – 20 ].…”
Section: Introductionmentioning
confidence: 99%